Markowitz portfolios under transaction costs - Olivier Ledoit; Michael Wolf (University of Zurich, Department of Economics, 2024)
Markowitz portfolio selection is a cornerstone in finance, in academia as well as in the industry. Most academic studies either ignore transaction costs or account for them in a way that is both unrealistic and suboptimal by (i) assuming transaction costs to be constant across stocks and (ii) ignoring them at the portfolio-selection state and simply paying them after the fact. Our paper proposes a method to fix both shortcomings. As we show, if transaction costs are accounted for (properly) at the portfolio-selection stage, net performance in terms of the Sharpe ratio often increases, in particular for high-turnover strategies.
Keywords: C13; G11; 330; Covariance matrix estimation; mean-variance efficiency; multivariate GARCH; portfolio selection; transaction costs